On Patrick White : Writers on Writers. - Tsiolkas, Christos (Schwartz Publishing Pty, Limited, 2018)
'Patrick White, the un-Australian writer who did more than any other writer in the twentieth century to create an imaginative language that we can call Australian, who unshackled us from the demand that we write as the English do, who recognised, through his own alienation and also through his profound love for his partner, that we were a migrant and mongrel nation forging our own culture and our own language.'-- --Erik Jensen on Kate Jennings Ceridwen Dovey on J.M. Coetzee (forthcoming) Nam Le on David Malouf (forthcoming) Michelle de Kretser on Shirley Hazzard (forthcoming).